Skin dendritic cell and T cell activation associated with dengue shock syndrome - Duyen, Huynh Thi Le (2018)
The pathogenesis of severe dengue remains unclear, particularly the mechanisms underlying the plasma leakage that results in hypovolaemic shock in a small proportion of individuals. Maximal leakage occurs several days after peak viraemia implicating immunological pathways. Skin is a highly vascular organ and also an important site of immune reactions with a high density of dendritic cells (DCs), macrophages and T cells. We obtained skin biopsies and contemporaneous blood samples from patients within 24 hours of onset of dengue shock syndrome (DSS), and from healthy controls. We analyzed cell subsets by flow cytometry, and soluble mediators and antibodies by ELISA; the percentage of migratory CD1a+ dermal DCs was significantly decreased in the DSS patients, and skin CD8+ T cells were activated, but there was no accumulation of dengue-specific antibodies. Inflammatory monocytic cells were not observed infiltrating the skin of DSS cases on whole-mount histology, although CD14dim cells disappeared from blood.